Loin des yeux, loin du cœur ? - Maria Caiata Zufferey (Socio-anthropologie, 2022)
This exploratory study illustrates the challenges and opportunities of remote qualitative research on sensitive issues. The analysis is based on the experience of fourteen researchers who have lived the digital switchover linked to the covid-19 pandemic as both a constraint and a resource. Based on exchanges in four focus groups, the participants identified tensions at the heart of remote qualitative research: the data collected lacks proxemic and contextual information, while benefiting from more discursive depth; interaction allows for a certain redistribution of power, but is accompanied by a loss of control on the part of the researcher; virtual distance favors the integrity and autonomy of the respondent, while hindering empathy and the ethic of care. Easy access and cost-effectiveness make remote research attractive, at the risk of generating new inequalities and superficial analyses. These results show that remote investigation on sensitive subjects is a paradoxical scientific practice, capable of both innovating and distorting the research process.